Optimization of catalyst composition in La0.75Ca0.25Cr0.5Mn0.5MxO3 for enhanced hydrogen production via methane cracking - Khan, Muhammad Hassan (Nanyang Technological University, 2024)
This study dives into the use of solid oxide fuel cell’s B-site doped La0.75Ca0.25Cr0.5Mn0.5MxO3 (LCCM, M = Fe, Co, Ni) anode material as a catalyst for methane cracking. From the array of doped catalysts, we will determine the optimal catalyst based on its carbon yield. The selection of LCCM is due to the stability in a redox atmosphere as well as the low carbon deposition on the LCCM anode when methane is used as a fuel for solid oxide fuel cell. It is expected that LCCM will serve as a very effective catalyst support, capable of efficiently diluting the catalyst to lower the degree of sintering during the catalyst preparation process, thereby enhancing the activity of the effective catalyst. In this study, the doped LCCM will be modified and be used as a self-supported catalyst for methane cracking to test its catalytic performance by optimizing catalyst preparation parameters. The transition metal cobalt, iron and nickel were doped into the B-site of LCCM to enhance the LCCM catalytic performance. The LCCM catalyst was produced using a modified solid-state reaction method, specifically the aqueous gel-casting method. The research results indicate that the catalytic activities of the 100Ni-LCCM is ideal in terms of the carbon yield obtained in the experiment. The carbon yield from XRD analysis, weight loss rate under H2 atmosphere and carbon yield from methane cracking proves to show that the 100Ni-LCCM is the ideal candidate for methane cracking.